Mania Following Bereavement: State of the Art and Clinical Evidence - Carmassi, Claudia; Shear, Katherine M.; Corsi, Martina; Bertelloni, Carlo Antonio; Dell’Oste, Valerio; Dell’Osso, Liliana (Frontiers in Psychiatry, 2020)
Bereavement is the state of loss, determined in most of the cases by the death of a close person. It is probably the greatest sorrow that can occur in an individual life. Grief is a normal, healthy response to loss, evolving through stages in the process of mourning. In some cases, bereavement may lead to the outburst of manic episode: despite literature data being scarce, reports have explored this important clinical entity, variously called as “funeral mania” or “bereavement mania”. We systematically reviewed the literature exploring the possible relationships between bereavement and the onset of a manic episode, both first or recurrent pre-existing episode, besides describing a case report on a manic episode in the aftermath of a loss event, with an accurate evaluation of prior mild mood spectrum instability, supporting the role of loss-events as potential risk factor for bipolar illness progression. This article tries summarizing existing evidence on the debate whether clinicians should consider mania as a possible bereavement reaction.